A theory of narrative - Altman, Rick, 1945- (New York : Columbia University Press, 2008)
What Is Narrative? -- The Song ... of Roland? -- Dual-Focus Narrative -- Hester's Speculation -- Single-Focus Narrative -- Pieter Bruegel, or the Space of Multiplicity -- Multiple-Focus Narrative -- Theoretical Conclusion -- Practical Conclusion.
Includes bibliographical references (p. 341-355) and index.
boek